Antimicrobial properties of green synthesis of MgO micro architectures via Limonia acidissima fruit extract. (March 2019) - Nijalingappa, T.B.; Veeraiah, M.K.; Basavaraj, R.B.; Darshan, G.P.; Sharma, S.C.; Nagabhushana, H.
Abstract: This paper reports a simple ecofriendly green combustion synthesis of magnesium oxide (MgO) micro architectures using various concentrations of Limonia acidissima fruit extract. The powder X-ray diffraction (PXRD) patterns of the as-formed product show single cubic phase and no further calcination was required. The crystallite size was obtained using Scherer's formula and was found to be 4–8 nm. The structural analysis was further analysed by Rietveld refinement technique. The morphology of combustion derived MgO micro architectures (NPs) were studied by using Scanning electron microscope. Various shaped nanostructures were obtained with different reaction parameters such as fuel concentration, pH and calcination temperatures. The Fourier transform infrared spectral studies reveal the various bond stretching in the prepared micro architectures. The growth mechanism for the formation of flower like structures were proposed. The diffuse reflectance spectral studies were carried out and energy band gap were estimated from the DRS spectra and the values ranges between (5.06–5.66 eV). Photoluminescence (PL) studies were carried upon exciting at 342 nm. A broad emission peak centered at ∼399 nm and 481 nm in the bluish-violet region was recorded. The Chromaticity diagrams were studied and found that MgO NPs emit bluish-violet color. Further, the obtained NPs were investigated for their antibacterial and antifungal activity. The results indicated that MgO NPs were effectively used as good candidates for antibacterial, waste water treatment, food safety applications and biomedical markers. Graphical abstract: Image 1 Highlights: MgO micro architectures were prepared via green synthesis route using Limonia acidissima fruit extract. Various morphologies were obtained with different pH and calcination temperatures. CIE and CCT results exhibit the MgO NSs were quite useful for the fabrication wLED's. The NSs exhibit superior antibacterial and antifungal activities.